UPAYA GURU AKIDAH AKHLAK DALAM PEMBINAAN PERILAKU KEAGAMAAN SISWA KELAS X AGAMA DI MADRASAH ALIYAH NEGERI PASER - Al Aziz Abdillah; Adiyono Adiyono (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
The research in this thesis is motivated by the large number of students who still violate the madrasa rules. Basically all teachers at MAN Paser have set a good example for students, but there are still many students who violate the rules in the madrasa. For example, there is some lack of respect for teachers by saying impolitely to teachers, mocking each other between students, lack of awareness to carry out obligations such as praying, reciting the Koran which still has to be reminded every day. This type of research is qualitative research. Data collected using the method of observation, interviews and documentation. The subjects in this study were the teachers of the Aqidah Akhlak subject, amounting to 1 person while the object was the teacher's efforts in fostering the religious behavior of students in Aqidah Akhlak subjects. After the authors conducted research with several methods to obtain results, namely: (1) Efforts by the teacher of aqidah morals in improving the religious behavior of students at MAN Paser, namely through habituation, providing religious understanding or insight and providing examples of good behavior, (2) Obstacles faced by the teacher aqidah morals in improving students' religious behavior that is influenced by external factors including environmental factors both in the family, school and community environment, (3) How to overcome the constraints of the teacher's aqeedah morals in increasing students' religious behavior at MAN Paser, namely by collaborating with guardians or other people parents of students, approaching students through school activities such as Ramadan activities and providing coaching actions such as giving advice and punishment.